THE IMPORTANCE OF PUBLIC INFORMATION IN THE EDUCATIONAL SYSTEM: Abdurazzakov Ilkhom Rustamovich, Hasanov Javokhir Tohir o’g’li, Toshmukhamadov Jasurbek Rustamovich - Termiz State Pedagogical Institute Teacher of the Department of Informatics; its Teaching Methodology, Abdurazzakov Ilkhom Rustamovich; Student of Termiz State Pedagogical Institute, Hasanov Javokhir Tohir o’g’li; Student of Termiz State Pedagogical Institute, Toshmukhamadov Jasurbek Rustamovich (Лучшие интеллектуальные исследования, 2024)
In this article, the information of the society in the modern world, the importance of information today and the work to be done in this area were discussed.